2004
DOI: 10.1128/jcm.42.5.2275-2278.2004
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofCandida albicansmRNA in Archival Histopathology Samples by Reverse Transcription-PCR

Abstract: The feasibility of detecting Candida albicans mRNA in formalin-fixed paraffin-embedded archival human histopathology specimens by reverse transcription-PCR (RT-PCR) was investigated. RT with gene-specific primers was used to detect five single-copy C. albicans gene transcripts, including those of two housekeeping genes, in oral candidiasis samples up to 8 years of age

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…To increase the sensitivity of mRNA detection, the number of PCR cycles was also increased from 30 to 45 cycles and the amount of template (CaADH2 cDNA) used for PCR amplification was doubled (to twice that used for detection of Ca18S rRNA and CaADH1 mRNA). Under this condition, only 3 of the 10 samples tested positive, suggesting differential expression for CaADH2 and similar results had also been reported by Beggs et al (12).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To increase the sensitivity of mRNA detection, the number of PCR cycles was also increased from 30 to 45 cycles and the amount of template (CaADH2 cDNA) used for PCR amplification was doubled (to twice that used for detection of Ca18S rRNA and CaADH1 mRNA). Under this condition, only 3 of the 10 samples tested positive, suggesting differential expression for CaADH2 and similar results had also been reported by Beggs et al (12).…”
Section: Discussionsupporting
confidence: 90%
“…Under this condition, only 3 of the 10 samples tested positive, suggesting differential expression for CaADH2 and similar results had also been reported by Beggs et al. .…”
Section: Discussionsupporting
confidence: 90%
“…Relative quantification of gene expression was performed using the comparative C T method (sequence detection systems chemistry guide; Applied Biosystems). The most stable housekeeping genes, EFB1 and ACT1 (11), across the sample states were chosen using the statistical technique described by Vandesompele et al (73). The internal normalization factor was the geometric mean of the stable housekeeping genes (73).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies had shown a positive correlation between epithelial dysplasia, oral squamous cell carcinoma and elevated level of Candida species in the oral cavity [24][25][26][27]. It had been demonstrated that oral candidosis may play a significant role in malignant transformation generally.…”
Section: Experimental Part Materials and Methodsmentioning
confidence: 99%